GOUVERNANCE BANCAIRE ET RENTABILITE FINANCIERE AU CAMEROUN - Robert, Tangakou Soh; ArsѐneFokwa; Belery, Merci (European Scientific Journal, ESJ, 2015)
This work is to study the effect of the Board on the performance of institutions credit in Cameroon. More specifically, it is to evaluate how the size of the board improves bank financial profitability Cameroon on the one hand and secondly to analyze the impact of the composition of the Board on bank financial profitability in Cameroon. The contribution of this study is that it examines the impact of organizational variables, in addition to financial and macroeconomic variables, mainly focusing on the role played by the Board of Directors on the financial viability of Cameroonian banks. The key findings emerged from this empirical study indicate that the involvement of the board as head of the institution seems to be positively correlated with the return on assets of banks and negatively correlated with the profitability of banks’ own funds on the reference period.